2018
DOI: 10.1155/2018/8408915
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Based Edible Coating Combined with Mentha pulegium Essential Oil as Bioactive Packaging for Strawberries

Abstract: The effect of gelatin-based edible coating incorporated with Mentha pulegium essential oil (MEO) on physicochemical (pH, titratable acidity (TA), weight loss, total soluble solids (TSS), and total phenolic content (TPC)), microbiological (total aerobic mesophilic flora (TAMF) and yeasts and moulds (YM)), and sensorial (color and firmness) characteristics of strawberries stored under refrigeration was studied. Strawberries were coated with gelatin alone (4%) and/or gelatin combined with two concentrations (0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 33 publications
3
21
0
3
Order By: Relevance
“…According to Burt (2004), these hydrophobic compounds penetrate the cell membranes of bacteria, disrupt the cell wall structures and make them more permeable, thereby leading to leakage of cellular materials concomitant to cell death. Our results are in agreement with the majority of published data on the antimicrobial activity of films and coatings impregnated with EOs (Aitboulahsen, Zantar, Laglaoui, et al, 2018; Ghasemlou et al, 2011; Hosseini et al, 2009; Nisar et al, 2018; Wu et al, 2017; Yanwong & Threepopnatkul, 2015). The antimicrobial activity of bioactive films depends on several factors including the conditions and methods of obtaining biopolymer‐based films, the formulation of the composites and the release of active compounds (Fernandez‐Saiz, Lagaron, Hernandez‐Muñoz, & Ocio, 2008; Gomez‐Estaca, Montero, Gimenez, & Gomez‐Guillén, 2007).…”
Section: Resultssupporting
confidence: 92%
“…According to Burt (2004), these hydrophobic compounds penetrate the cell membranes of bacteria, disrupt the cell wall structures and make them more permeable, thereby leading to leakage of cellular materials concomitant to cell death. Our results are in agreement with the majority of published data on the antimicrobial activity of films and coatings impregnated with EOs (Aitboulahsen, Zantar, Laglaoui, et al, 2018; Ghasemlou et al, 2011; Hosseini et al, 2009; Nisar et al, 2018; Wu et al, 2017; Yanwong & Threepopnatkul, 2015). The antimicrobial activity of bioactive films depends on several factors including the conditions and methods of obtaining biopolymer‐based films, the formulation of the composites and the release of active compounds (Fernandez‐Saiz, Lagaron, Hernandez‐Muñoz, & Ocio, 2008; Gomez‐Estaca, Montero, Gimenez, & Gomez‐Guillén, 2007).…”
Section: Resultssupporting
confidence: 92%
“…This is because TOE has hydrophobic properties and reduces the transference of water vapor through the coating [27]. According to the literature, the effect of gelatin coating with TOE produced similar effects in other studies, where gelatin has proven to be more effective when mixed with hydrophobic components [28]. Based on the results shown in this research, it is inferred that gelatin coatings with TOE retard the metabolic processes of the fruit and, therefore, extend its shelf life in cold storage.…”
Section: Weight Losssupporting
confidence: 79%
“…Pec-based edible coatings containing additives (such as anti-browning, apple fiber, and antioxidants) [ 20 , 40 ], as well as CMC [ 17 ] led to the accumulation of phenolic compounds. A positive effect of different coatings (alone or in combination with additives) on total phenolics has been reported [ 22 , 24 , 36 , 43 ]. Panahirad et al [ 8 ] reported a negative effect of CMC on total phenolics, and a positive effect on anthocyanins and flavonoids contents.…”
Section: Discussionmentioning
confidence: 99%